Analysis of daily rainfall to determine the pattern of madden julian oscillation (MJO) phenomenon in the areas around the Indonesian equators - Afni Nelvi (PILLAR OF PHYSICS, 2014)
Madden Julian Oscillation (MJO) plays an important role as the Intraseasonal Variaton (ISV) that can affect the amount of rainfall. Knowing phenomena of oscillation as the MJO provides benefits to determine the approximate rainfall in the foreseeable future. Therefore, the authors are interested in researching on daily rainfall analysis to determine the pattern of the phenomenon of MJO in the area around the Equator Indonesia including Padang, Pekanbaru, Pontianak and Palu in 2003-2012. This research is descriptive research. This research data is a daily rainfall data for areas of Padang, Pekanbaru, Pontianak and Palu of the years 2003-2012. The data processing is done using Microsoft Excel, Weighted Wavelet Z-Transform (WWZ) and surfer 8. Based on the results of data processing, Padang and Pontianak having a pattern of rainfall equatorial, Pekanbaru having a pattern of rainfall monsunal while Palu having the pattern of rainfall pattern local. A pattern of oscillations MJO in the field and Pekanbaru active in phase 3, in Pontianak active in phase 4 and in the Palu active in phase 5. Impacts generated oscillations MJO in phase active is rainfall will high in the area which behind him during propagation of the Indian Ocean to the Pacific Ocean. The accident time MJO in Padang are more dominant than to the areas of Pekanbaru, Pontianak and a Palu, with 36 times. MJO in Pekanbaru happens as many as 15 times, in Pontianak happens as many as 26 times and in the Palu happens as many as 16 times